PENGUKURAN TINGKAT PRODUKTIVITAS INDUSTRI KERIPIK TEMPE âSUKA NICKYâ BANJARNEGARA MENGGUNAKAN METODE MARVIN E MUNDEL - , RATNA YUNIAR P. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Produktivity measurement is done by measuring the level of partial and total produktivity of the company, as well as determining the index produktivity in intdustrial tempeh chips âSuka Nickyâ during the periode of Juli â August 2014, so can be measured the perormance of the industry. Produktivity measurements using method Marvin E Mundel. Marvin E Mundel is a method that uses the approach of index numbers, so it can be measured periode of produktivity measurement and compared with the base period to knowing the trend of increasing and decreasing over time. By using productivity measurement methode Marvin E Mundel, it can be seen index partial and index total productivitytends to increase each periode compared with the base period. Index produktivity in second week to the fifth week of an increase because an increase in each of the partial produktivity. But in sixth weekof a declice in the total productivity is influenced by the decreas in the partial productivity of capital and maintenance. The seventh period is also decreased the total productivity because all of partial produktivity is decreased axcept the partial productivity energi and labor. In the eighth and ninth weeks showed an increasein total productivity because in increase the productivity in each partial.